Constructing Women's Leadership Representation in the UK Press During a Time of Financial Crisis: Gender capitals and dialectical tensions. Issue 1 (January 2018) - Elliott, Carole; Stead, Valerie
A continuing challenge for organizations is the persistent underrepresentation of women in senior roles, which gained a particular prominence during the global financial crisis (GFC). The GFC has raised questions regarding the forms of leadership that allowed the crisis to happen and alternative proposals regarding how future crises might be avoided. Within this context women's leadership has been positioned as an ethical alternative to styles of masculinist leadership that led to the crisis in the first place. Through a multimodal discursive analysis this article examines the socio-cultural assumptions sustaining the gendering of leadership in the popular press to critically analyse how women's leadership is represented during the GFC of 2008–2012. Highlighting the media's portrayal of women's leadership as a gendered field of activity where different forms of gender capital come into play, we identify three sets of dialectics: women as leaders and women as feminine, women as credible leaders and women as lacking in credibility, and women as victims and women as their own worst enemies. Together, the dialectics work together to form a discursive pattern framed by a male leadership model that narrates the promise of women leaders, yet the disappointment that they are not men. Our study extends understandings regarding how female and feminine forms of gender capital operate dialectically, where the media employs feminine capital to promote women's positioning as leaders yet also leverages female capital as a constraint. We propose that this understanding can be of value to organizations to understand the impact and influence of discourse on efforts to promote women into leadership roles.